1994
DOI: 10.1016/0014-5793(94)00784-5
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of zeaxanthin and antheraxanthin reverses non‐photochemical quenching of photosystem II chlorophyll a fluorescence in the presence of trans‐thylakoid ΔpH

Abstract: The xanthophyll cycle apparently aids the photoprotection of photosystem II by regulating the nonradiative dissipation of excess absorbed light energy as heat. However, it is a controversial question whether the resulting nonphotochemical quenching is soley dependent on xanthophyll cycle activity or not. The xanthophyll cycle consists of two enzymic reactions, namely deepoxidation of the diepoxide violaxanthin to the epoxide-free zeaxanthin and the much slower, reverse process of epoxidation. While deepoxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
2
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 20 publications
2
45
2
2
Order By: Relevance
“…Our data are partly in contrast to the earlier reported direct correlation of the DEPS and the pH-dependent qN in whole thylakoids (Gilmore and Yamamoto, 1993;Gilmore et al, 1994), which suggested that the whole xanthophyll pool (and not only those xanthophylls that are bound to Lchbl-3 and Lhcb5/6) reacts with the same kinetics and is involved in qE. Here we show that the DEPS in Lhcb4 and PSI shows clearly different behavior in comparison with the other antenna complexes and also the leve1 of qE.…”
Section: Determination Of Qn Parameterscontrasting
confidence: 56%
See 1 more Smart Citation
“…Our data are partly in contrast to the earlier reported direct correlation of the DEPS and the pH-dependent qN in whole thylakoids (Gilmore and Yamamoto, 1993;Gilmore et al, 1994), which suggested that the whole xanthophyll pool (and not only those xanthophylls that are bound to Lchbl-3 and Lhcb5/6) reacts with the same kinetics and is involved in qE. Here we show that the DEPS in Lhcb4 and PSI shows clearly different behavior in comparison with the other antenna complexes and also the leve1 of qE.…”
Section: Determination Of Qn Parameterscontrasting
confidence: 56%
“…has been suggested by severa1 authors (Demmig-Adaws et al, 1990;Gilmore and Yamamoto, 1993;Gilmore et al, 1994;Jahns and Schweig, 1995;Horton et al, 1996). Binding of the xanthophyll-cycle pigments by antenna proteins (Bassi et al, 1993;Ruban et al, 1994;Lee and Thornber, 1995) supports the attribution of qE to events in the PSII antenna.…”
mentioning
confidence: 56%
“…Thermal dissipation measured as non-photochemical PSII fluorescence quenching (NPQ) is triggered by the trans-thylakoidal proton gradient ( pH) and zeaxanthin (ZEA) synthesis through the xanthophyll cycle (Gilmore et al, 1994) and is recognized as the most important photoprotective mechanisms in higher plants and several algal divisions (Rodrigues et al, 2002). Fucoxanthin and violaxanthin levels were not affected in C. compressa whereas in P. pavonica fucoxanthin and violaxanthin increased under 70% PAB conditions, nutrient enrichment and medium CO 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this cycle, violaxanthin is deepoxidised in two steps to zeaxanthin by a luminally located deepoxidase, and the reverse epoxidation is catalysed by a stromal epoxidase. It has been shown (e.g., Pfündel and Dilley, 1993) that the deepoxidation reaction is strongly dependent on the luminal pH, whereas the epoxidation reaction is independent (Gilmore et al, 1994). These findings are incorporated into the model by a simplified description of the xanthophyll cycle, in which a quencher can be either inactive or active (denoted N 0 and N , respectively) and the total amount of quencher is assumed to be constant and is normalised to unity, N + N 0 = 1.…”
Section: Modelmentioning
confidence: 99%